The agricultural development of the 1820 settlement down to 1846 - Webb, Arthur (Arthur C M) (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1975)
Preface: The arrival of the 1820 Settlers in South Africa and their impact on the political and social life of the Cape Colony has been well covered by historical research. This work is an attempt to illuminate yet another area in which their impact was felt. The failure of the settlement scheme under which these people were introduced into the colony has tended to detract from the importance which agriculture played in the early years of their residence in South Africa. The failure of the first crops may well have ended the attempts by many to establish themselves on the land but for others it was the beginning of a process of adaptation to the agricultural conditions of a new country. In this they were remarkably successful and within a decade the English farming community of the eastern frontier was prospering. The theme of this work traces the progress of these farmers through the initial period of crop failures, which condemned the settlement in the eyes of many, and through the ensuing years and later misfortune, the Sixth Frontier war of 1834-35. Both these setbacks were very significant in moulding the development of agriculture as practised by these farmers. In the past, historians have tended to over-estimate the reverse suffered by these farmers during this frontier war. The seemingly paradoxical questions raised by the rapid recovery of this community after the war have been left largely unanswered. Some attempt is made in the pages which follow to shed new light on this issue. In the first three chapters of this work the letters written by Thomas Philipps to his family in Britain form the chief source of information. Much of this correspondence has already found wider publication in a volume edited by Arthur Keppel-Jones, but there are significant omissions, particularly with regard to Philipps' commentary on agricultural matters. Unfortunately, this series of letters ends in 1830, and the chief sources for the latter period of this work are the various entries made) on agricultural matters, in the Graham's Town Journal, together with the farm diary of James Collett, another frontier farmer. From these, and various other works, it has been possible to trace the major developments of this farming community.
Keywords: Agriculture -- South Africa -- Eastern Cape -- History; Agricultural colonies -- South Africa -- Eastern Cape; British settlers of 1820 (South Africa); Cape of Good Hope (South Africa) -- History -- 1795-1872